2001
DOI: 10.1097/00000542-200101000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Orally Administered Sustained- release Hydromorphone in Humans

Abstract: A single oral dose of a new sustained-release formulation of hydromorphone provided analgesia to experimental pain beyond 24 h of its administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 1 publication
3
70
0
Order By: Relevance
“…Each pain tolerance value was the median of five subsequent measurements obtained at intervals of 1 min. This pain model has been demonstrated previously to be suitable for quantifying analgesic effects of strong opioids [32][33][34][35].…”
Section: Figurementioning
confidence: 99%
“…Each pain tolerance value was the median of five subsequent measurements obtained at intervals of 1 min. This pain model has been demonstrated previously to be suitable for quantifying analgesic effects of strong opioids [32][33][34][35].…”
Section: Figurementioning
confidence: 99%
“…29 This issue is not unique to hydromorphone but is shared with other hydrophilic opioids (eg, morphine with its combined transfer half-life of 10 hours, with its active morphine 6-glucuronide metabolite). 17 In contrast, the lipophilic opioids have far shorter transfer half-lives (fentanyl, 5 minutes), …”
Section: Pharmacokinetic Factors Causing Drug Accumulation In Serum Amentioning
confidence: 99%
“…In addition, patient 4 once again underscores the problem with accumulation of the hydromorphone in the CNS from too frequent of a dosing interval in relationship to transfer half-life. 29 Unfortunately, the drug reached its peak effect in the CNS only after the patient was discharged, resulting in his death at home. Furthermore, patient 4 also demonstrates the synergistic effect of alcohol (decreasing hypoxic drive) 37,38 while the concomitant administration of the opioid produced a rightward shift in the end-expiratory CO 2 concentration.…”
Section: Drug-drug Drug-disease Synergymentioning
confidence: 99%
“…Angst et al [5] studied the pharmacokinetics and pharmacodynamics of sustained-release hydromorphone in healthy volunteers subjected to experimental pain and compared that with the results seen with the immediaterelease formulation. They found that the hydromorphone plasma concentration peaked significantly later, but was maintained significantly longer (at more than 50% of peak concentration) after sustained-release than after immediate-release hydromorphone.…”
Section: Hydromorphonementioning
confidence: 99%